2017
DOI: 10.1534/g3.117.040717
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Imputation To Improve the Cost-Efficiency of Genomic Selection in Farmed Atlantic Salmon

Abstract: Genomic selection uses genome-wide marker information to predict breeding values for traits of economic interest, and is more accurate than pedigree-based methods. The development of high density SNP arrays for Atlantic salmon has enabled genomic selection in selective breeding programs, alongside high-resolution association mapping of the genetic basis of complex traits. However, in sibling testing schemes typical of salmon breeding programs, trait records are available on many thousands of fish with close re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 49 publications
11
96
1
Order By: Relevance
“…However, the use of genotyping strategies exploiting a combination of low‐ and medium‐ density SNP panels and genotype imputation have proven effective in increasing selection accuracy compared to PBLUP while minimizing the costs of genotyping, thus representing a cost‐effective alternative for the implementation of GS in aquaculture species (Tsai et al . ; Yoshida et al . 2018b).…”
Section: Incorporation Of Genomicsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the use of genotyping strategies exploiting a combination of low‐ and medium‐ density SNP panels and genotype imputation have proven effective in increasing selection accuracy compared to PBLUP while minimizing the costs of genotyping, thus representing a cost‐effective alternative for the implementation of GS in aquaculture species (Tsai et al . ; Yoshida et al . 2018b).…”
Section: Incorporation Of Genomicsmentioning
confidence: 99%
“…Although there is null published information about objective economical appraisal of the implementation of GS in aquaculture breeding programmes, the development and implementation of effective genotype imputation strategies will promote the establishment of cost‐effective GS for traits that are difficult to measure in selection candidates (Tsai et al . ; Yoshida et al . 2018b).…”
Section: Future Challenges and Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…the offspring) at very-low density, but impute to high density -a technique that is relatively commonplace in terrestrial livestock breeding (e.g. Wellmann et al, 2013) and has shown promise in Atlantic salmon breeding (Tsai et al, 2017).…”
Section: Future Directionsmentioning
confidence: 99%